The two horizons Old Testament commentary : Job - Wilson, Lindsay, 1955- (Grand Rapids, MI, William B Eerdmans Publishing Company, 2015)
In this commentary Lindsay Wilson shows the book of Job to be a coherent literary work that addresses this question: Is it possible for humans to have genuine faith in God regardless of their circumstances? Wilson argues that Job's bold, sometimes questioning cries to God are portrayed as legitimate expressions of trust for a righteous person in adversity. Through critical exegesis of the text, Wilson focuses on the message of Job and its implications for practical ministry, examining such key issues as suffering, justice, lament, and faith. He also touches on various pertinent topics in Christian ethics, including individual character, wealth, suicide, and the environment. In a final section Wilson offers guidance on using Job as a resource book for pastoral care and prayer, and he discusses how to teach and preach from the book of Job. - Amazon
Acknowledgments -- Abbreviations. Introduction. Who Wrote the Book, and When Was It Written? -- Are These Real Historical Events and the Actual Words Spoken? -- How Should We Read the Book? -- Why Was the Book Written? -- How Have Others Understood It? -- How Do the Different parts of the Book Fit Together? -- What is the Structure of the Book? -- Is the Text of Job Reliable? -- Why Is the Book So Long and Repetitive?. Commentary. 1:1 -- 2:13: The Prologue -- 3:1-31:40: The Dialogue -- 32:1 -- 42:6: The Verdicts -- 42:7-17: The Epilogue. Theological Themes. Suffering -- Retribution and Justice -- The Litigation Motif -- Lament and Complaint to God -- Persevering Faith -- The Fear of God -- Humanity -- God -- Creation. Job and Theology. Job and Biblical Theology -- Job and Systematic Theology -- Job and Moral Theology -- Job and Practical Theology. Bibliography. Index of Authors. Index of Scripture References.
Includes bibliographical references (pages 385-395) and index.
Keywords: Bible. -- Commentaries; Bible. -- Theology; Commentaries